Leishmaniose tegumentar americana e suas relações sócio ambientais no município de Ubatuba-SP - Ana Elisa Pereira Silva; Helen da Costa Gurgel (Confins)
The American Cutaneous Leishmaniasis (ACL) is a vetorial disease that can be acquired when anyone is bitten by an infected mosquito. The majority of the cases occur in Northern parts of Brazil, although in the north of the Sao Paulo coast line, a touristic area, the number of cases is also high. In order to understand the influence of social and environmental changes in the dynamics of the illness, we analyzed the space-time distribution of the cases registered between 1998 and 2006 in Ubatuba-SP. This was analyzed using geoprocessing techniques and remote sensing, as well as the land use and the climate variability. In 2003 the number of cases reach its peak and this reason motivated the development of this assignment. The raining season in 2003 occurred only in the first months of the summer. The warm and humid climate contribute to increase sandflies. The results showed that the illness seems to affect workers in general (masculine). However, important relationship between land use dynamics and illness place and also the distance to households and forest was found. The social factor also seems related because the home values are usually lower in suburbs near the forest, where is high incidence of vector mosquito. The dynamics of the disease also receives demographic and economic influence, mainly related to the choice households, often motivated by economic situation.